A Perceptual Analysis of Vowel Elision in Educated Ekiti English - Aluko, Busuyi Stephen (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Nigerian English, with its own varieties which include Ekiti English, has its own peculiar features at the levels of lexis, syntax, semantics and phonology. Some scholarly attempts have been made at characterising these features. This study, another attempt in this direction, investigates Elision in Educated Ekiti English with a view to finding out how educated Ekiti users of English employ elision in their speeches. Data for the study were gathered through structured texts read into a tape recorder by fifty respondents (civil servants in the Ekiti State Ministry of Education) purposively selected. Data generated were later analysed using perceptual analysis and simple percentage. The study reveals that there are insignificant cases of elision in Educated Ekiti English. A low percentage of the subjects realised elision in words tested that contained vowels that were expected to be elided. Therefore, Educated Ekiti speakers of English do not usually make use of elision in their speeches as they tend to pronounce every word as it appears.